A model for the relationship between wing fray and chronological and ovarian ages in tsetse (Glossina spp). Issue 3 (28th March 2020) - Hargrove, J. W.
Abstract: Age‐dependent mortality changes in haematophagous insects are difficult to measure but are important determinants of population dynamics and vectorial capacity. A Markov process was used to model age‐dependent changes in wing fray in tsetse ( Glossina spp), calibrated using published mark–recapture data for male G. m. morsitans in Tanzania. The model was applied to female G. m. morsitans, captured in Zimbabwe using a vehicle‐mounted electric net and subjected to ovarian dissection and wing fray analysis. Rates of fray increased significantly with age in males but not females, where the rate was constant for ovarian categories 0–3. A jump in mean fray between ovarian categories 3 and 4 + 4 n is consistent with the latter category including flies that have ovulated 4, 8, 12, 16 times and so on. The magnitude of the jump could, theoretically, facilitate improved mortality estimates. In practice, although knowledge of fly mortality was required for modelling wing fray, mortality estimates derived from ovarian dissection data are independent of patterns and rates of change in wing fray. Significantly better fits to ovarian age data resulted when age‐specific mortality was modelled as the sum of two exponentials, with high mortality in young and old flies, than when mortality was constant at 2.3% per day. Abstract : During their first three pregnancies, the age of female tsetse can be estimated accurately using ovarian dissection. Thereafter, ovarian dissection cannot be used to distinguish between flies in their first and later ovarian cycles. Flies in later cycles would, however, have higher mean levels of wing fray. A Markov model was developed for age‐dependent changes in fray for known‐aged males released and recaptured in the field. The same model was used to model the relationship between ovarian age and wing fray categories in females. This model provided improved age distributions of field tsetse and could lead to better mortality estimates.